Décadence : "Decline and Fall" or "Other Antiquity"?. - Formisano, Marco; Fuhrer, Therese; Stock, Anna-Lena. (Heidelberg : Universitätsverlag Winter, 2014)
No scholar today would describe late antiquity as an age of "decline and fall", as Gibbon did; instead, to use Marrou's term, it is seen as an "other antiquity", which deserves to be investigated on its own terms. Yet the idea of a decadent period, accompanied by a fascination for the image of antiquity on the wane, continues to live in scholarly minds, as is suggested, after all, by the recurring insistence on the point that late antiquity was not a period of decline. This collection of papers engages in a productive way with the fascination exerted by the concept of an era in decline and a l.
Andreas T. Zanker: Decline and Kunstprosa -- Velleius Paterculus and Eduard NordenNotes on Contributors; Index locorum; 1.) Scripture; 2.) Ancient Literature; 3.) Medieval and Early Modern Literature; 4.) Modern Literature; Index nominum et rerum.
Print version record.
Includes bibliographical references and indexes.
Contributions in English, French, and German.
eBooks on EBSCOhost
Keywords: Classical literature -- History and criticism -- Congresses; Civilization, Greco-Roman -- Congresses; Degeneration in literature -- Congresses; Littérature ancienne -- Histoire et critique -- Congrès.; Civilisation gréco-romaine -- Congrès.; Dégénérescence dans la littérature -- Congrès.; Civilization, Greco-Roman; Classical literature; Degeneration in literature; Spätantike; Kultur; Niedergang; Antike; Dekadenz; Untergang; Antik litteratur -- historia; Kulturhistoria; Conference papers and proceedings; Criticism, interpretation, etc